2017
DOI: 10.1021/acs.joc.7b01042
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Generation of Quinolinium Ylides from Diazo Compounds: Copper-Catalyzed Synthesis of Indolizine

Abstract: The Cu-catalyzed three-component reaction between quinolines, diazo compounds, and alkenes has been established for direct construction of indolizine derivatives via quinolinium ylides. This methodology is distinguished by the use of a commercially inexpensive catalyst and readily available starting materials, wide substrate scope, and operational simplicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(20 citation statements)
references
References 79 publications
0
20
0
Order By: Relevance
“…Traditional synthetic routes to indolizines mainly comprise the Scholtz or Chichibabin reactions. More recently, cycloaddition reactions (1,3‐dipolar cycloadditions), intramolecular cyclizations using acetic anhydride, formation of C3–C4 bond, formation of C1–C9 bond, and formation of C8–C9 bond have been reported . However, most of these methods suffer from some drawbacks, such as the formation of conjugate‐acid waste, narrow substrate scope, harsh reaction conditions, need for toxic transition‐metal catalysts and harmful organic solvents.…”
Section: Methodsmentioning
confidence: 99%
“…Traditional synthetic routes to indolizines mainly comprise the Scholtz or Chichibabin reactions. More recently, cycloaddition reactions (1,3‐dipolar cycloadditions), intramolecular cyclizations using acetic anhydride, formation of C3–C4 bond, formation of C1–C9 bond, and formation of C8–C9 bond have been reported . However, most of these methods suffer from some drawbacks, such as the formation of conjugate‐acid waste, narrow substrate scope, harsh reaction conditions, need for toxic transition‐metal catalysts and harmful organic solvents.…”
Section: Methodsmentioning
confidence: 99%
“…In 2017, Wan et al reported a Cu-catalyzed one-pot reaction for a simple construction of indolizine derivatives with quinolines, diazo compounds and electrophilic alkenes (Scheme 13). [26] A variety of diazoesters 33 were well tolerated under this catalytic system along with 71 examples under mild conditions in open air. In their mechanism study, the initially formed adduct 39 a rather than product 40 a was detected by LC-MS and intermediate 39 a was isolated in 56% yield when the control reaction was conducted under a N 2 atmosphere (Scheme 13, bottom part).…”
Section: Cu-catalyzed [3 + 2]-cycloadditionmentioning
confidence: 95%
“…Oxime acetate (45) was used with toluene derivatives (Scheme 17), which produced trisubstituted pyridine 47. [31] Benzylamine and p-toluenesulfonylhydrazone could also furnish the desired product when used as a substitute for toluene.…”
Section: Pyridine Synthesismentioning
confidence: 99%
“…Wan and co-workers reported indolizine formation by in situ generated quinolium ylides from diazo compounds (Scheme 31b). [45] This three-component reaction proceeds through a copper carbene species which forms pyridinium ylide intermediate.…”
Section: Indolizine Synthesismentioning
confidence: 99%